Pretreatment with rumen fluid improves methane production in the anaerobic digestion of paper sludge. (August 2018) - Takizawa, Shuhei; Baba, Yasunori; Tada, Chika; Fukuda, Yasuhiro; Nakai, Yutaka
Highlights: Detergent fibers are hydrolyzed during pretreatment with rumen fluid. Pretreatment with rumen fluid increases the volatile fatty acids during anaerobic digestion. Pretreatment with rumen fluid enhances the methane production from paper sludge by 3.4 times. Abstract: Because paper sludge discharged from the waste paper recycling process contains high levels of lignin and ash, it is not hydrolyzed effectively during anaerobic digestion. In this study, we investigated the effects of pretreatment with rumen fluid on paper sludge and on the methane fermentation process. Paper sludge was pretreated with rumen fluid at 37 °C for 6 h. Following pretreatment, 4.5% of the total solids in paper sludge were degraded and converted, and the dissolved chemical oxygen demand and volatile fatty acid concentration increased. Batch methane fermentation was conducted at 37 °C for 20 days. During methane fermentation, the degradation and hydrolysis of paper sludge were enhanced by pretreatment with rumen fluid. The amounts of total methane production from pretreated paper sludge (excluding methane generated from rumen fluid), rumen fluid and untreated paper sludge were 650.4, 819.9 and 190.8 ml, respectively. The volume of methane gas produced from pretreated paper sludge was 3.4 times larger than that from untreated paper sludge. These results indicate that pretreatment with rumen fluid enhances methane production from paper sludge.